Tindak Pidana Ekonomi Transnasional: Tinjauan Hukum dan Implikasi Sosial - Khadirin; Ani Purwati (Jurnal Riset Multidisiplin Edukasi, 2025)
This study examines transnational economic crimes as increasingly complex cross-border offenses in the era of globalization, focusing on money laundering, international corruption, and the illegal trade of natural resources. These crimes not only harm the national economy through loss of foreign exchange and market distortion but also threaten social stability, undermine public trust, and weaken law enforcement. Indonesia has established a legal framework through Law No. 8 of 2010 on the Prevention and Eradication of Money Laundering, Law No. 20 of 2001 on the Eradication of Corruption, and Law No. 4 of 2009 on Mineral and Coal Mining, while actively participating in international cooperation such as the Financial Action Task Force (FATF) and the United Nations Convention against Transnational Organized Crime (UNTOC). Using Roscoe Pound’s “Law as a Tool for Social Engineering” theory, this research highlights the importance of integrating the flexibility of the Anglo-Saxon legal system with the strong regulatory framework of the Continental system. The findings emphasize the need to strengthen coordination among law enforcement agencies, enhance forensic investigation technologies, harmonize regulations with international standards, and implement legal measures that incorporate social justice and local wisdom to ensure effective and sustainable crime prevention.